P595 Vaginal microbiota among adolescent and young adult women with pelvic inflammatory disease. (14th July 2019) - Trent, Maria; Perin, Jamie; Matson, Pamela; Gaydos, Charlotte
Abstract : Background: Pelvic Inflammatory Disease (PID) is a polymicrobial infection currently treated using syndromic management with broad-spectrum antibiotics. There are limited data describing the vaginal microbiota among adolescent and young adult women with PID, and how the post-PID microbial state may predispose to subsequent infection due to ongoing infection and shifts in vaginal microbiota. The purpose of this pilot research is to examine the microbial environment among adolescent and young adult women with acute PID. Methods: This analysis utilizes stored samples from 13–25-year-old patients (n=26) diagnosed with acute PID and enrolled in the Technology Enhanced Community Health Nursing (TECH-N) study, a large randomized controlled clinical trial designed to test a multi-faceted intervention for prevention of PID. Vaginal microbiota was characterized by 16S rRNA gene sequencing (V3-V4 regions) and clustered into community state types (CSTs). Results: At baseline, the majority of patients with acute PID were in a low-Lactobacillus or L.iners dominated state (CST I (L. crispatus dominated (N=3, 11.54%), CST III L. iners-dominated (N=7, 26.9%), CST IV Low-Lactobacillus (N=15, 57.69%), CST V L. jensenii-dominated (N=1, 3.85%)). The single CST V case had a relatively low abundance (55%) of L. jensenii. Conclusion: Preliminary vaginal microbiota testing among AYA with PID revealed over 1/2 of participants had a low abundance of Lactobacillus spp indicative of bacterial vaginosis and risk to STI. Over 1/4 had L. iners-dominated microbiotas, which are also often associated with BV. Lactobacillus spp and are thought to protect against pathogens; however, the level of protection may vary by strain. Additional research should examine these findings in larger samples, include PID-negative patients for comparison, and assess the changes in the vaginal microbiota associated with successful clearance of pathogens. Such work may improve understanding of the vaginal microenvironment during PID and elucidate a path to shift from syndromic management to precision treatment among affected patients. Disclosure: No significant relationships.